2005
DOI: 10.1136/jnnp.2004.042176
|View full text |Cite
|
Sign up to set email alerts
|

Long-term treatment of generalised myasthenia gravis with FK506 (tacrolimus)

Abstract: Efficacy and safety of long term use of FK506 (2-4.5 mg/ day) for a maximum of two years were evaluated in 12 patients with generalised myasthenia gravis (MG). At the end of the study, eight patients (67%) showed improvement in either MG score or Activities in Daily Living score, and prednisolone dosage could be reduced in seven patients (58%), with a mean reduction ratio of 37%. Long term use of FK506 for MG can be more effective than short term administration, with no serious side effects.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
55
0
2

Year Published

2006
2006
2015
2015

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 68 publications
(62 citation statements)
references
References 12 publications
4
55
0
2
Order By: Relevance
“…Various clinical situations have been studied, such as in patients refractory to, or intolerant of, corticosteroids or additional immunosuppression, presence of thymoma, and in patients with a relatively new diagnosis. The most common dosing strategies were: a fixed daily dose of 3 mg with or without assessment of trough drug concentrations; and a weight-based approach of 0.1 mg/kg/day in divided doses with dosage titrated to achieve a trough concentration of 7-8 ng/ml [Shimojima et al 2006;Nagaishi et al 2008;Tada et al 2006;Konishi et al 2003Konishi et al , 2005Zhao et al 2011;Yoshikawa et al 2011;Ponseti et al 2005aPonseti et al , 2005bPonseti et al , 2006Nagane et al 2005;Mitsui et al 2007]. While the weight-based regimen is within the manufacturer's dosing recommendations for prevention of transplant rejection, the 3 mg dose falls below the FDA-approved dosing range [Astellas Pharma, 2013].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Various clinical situations have been studied, such as in patients refractory to, or intolerant of, corticosteroids or additional immunosuppression, presence of thymoma, and in patients with a relatively new diagnosis. The most common dosing strategies were: a fixed daily dose of 3 mg with or without assessment of trough drug concentrations; and a weight-based approach of 0.1 mg/kg/day in divided doses with dosage titrated to achieve a trough concentration of 7-8 ng/ml [Shimojima et al 2006;Nagaishi et al 2008;Tada et al 2006;Konishi et al 2003Konishi et al , 2005Zhao et al 2011;Yoshikawa et al 2011;Ponseti et al 2005aPonseti et al , 2005bPonseti et al , 2006Nagane et al 2005;Mitsui et al 2007]. While the weight-based regimen is within the manufacturer's dosing recommendations for prevention of transplant rejection, the 3 mg dose falls below the FDA-approved dosing range [Astellas Pharma, 2013].…”
Section: Discussionmentioning
confidence: 99%
“…The long-term effects of the use of tacrolimus for MG management were assessed in several trials [Shimojima et al 2006;Nagaishi et al 2008;Tada et al 2006;Konishi et al 2005;Ponseti et al 2005aPonseti et al , 2005bPonseti et al , 2006Nagane et al 2005]. These trials consistently showed positive effects on the QMGS or a reduction in adjunct therapies, and followed patients on tacrolimus for up to a period of 5 years.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…It is used to control rejection after kidney, liver, heart, and bone marrow transplantation, and is also used to control graftversus-host disease. In Japan, tacrolimus is additionally employed to treat myasthenia gravis [13,14], rheumatoid arthritis [15], and atopic dermatitis (as a topical preparation) [16]. Regarding the efficacy of tacrolimus for lupus nephritis, it has been shown to prolong survival and decrease proteinuria in murine models of SLE (MRL/lpr mice and NZB/NZWF1 mice) [17].…”
Section: Introductionmentioning
confidence: 99%